Motor disturbances and thalamic electrical power of frequency bands' improve by grape seed extract in animal model of Parkinson's disease - Alireza Sarkaki; Zainab Eidypour; Freshteh Motamedi; keivan keramati keramati; Yaghoub Farbood (Avicenna Journal of Phytomedicine, 2012)
Objective: Previous studies showed that grape seed extract (GSE) is an excellent natural substance with potent antioxidant effect and free radical scavenger. This study aimed to evaluate the effect of GSE on motor dysfunctions and thalamic local Electroencephalography (EEG) frequency bands' powers in rats with Parkinson's disease (PD). Materials and Methods: In this study 8 µg 6-hydroxydopamine (6-OHDA) dissolved in 2 µl normal saline containing 0.01% ascorbic acid was infused into right medial forebrain bundle (MFB) to make an animal model of PD. Rats with PD received four weeks GSE (100 mg/kg, p.o.) after apomorphine-induced rotation test. Spontaneous motor tests and also thalamic ventroanterior nucleus (AV) local EEG recording were done in freely moving rats in all groups. Results: Chronic treatment of PD rats with GSE could influence potentially frequency bands' powers of thalamic VA and improve post-lesion motor dysfunctions significantly (p